2013
DOI: 10.5483/bmbrep.2013.46.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Transduced PEP-1-FK506BP ameliorates corneal injury in Botulinum toxin A-induced dry eye mouse model

Abstract: FK506 binding protein 12 (FK506BP) belongs to a family of immunophilins, and is involved in multiple biological processes. However, the function of FK506BP in corneal disease remains unclear. In this study, we examined the protective effects on dry eye disease in a Botulinum toxin A (BTX-A) induced mouse model, using a cell-permeable PEP-1-FK506BP protein. PEP-1-FK506BP efficiently transduced into human corneal epithelial cells in a time- and dose-dependent manner, and remained stable in the cells for 48 h. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…To remove endotoxins of proteins, purified control PON1 and PEP-1-PON1 were treated with a Detoxi-Gel™ endotoxin removing gel (Pierce, Rockford, IL, USA) as per manufacturer’s instructions [34]. The Bradford assay was used to estimate protein concentration [37].…”
Section: Methodsmentioning
confidence: 99%
“…To remove endotoxins of proteins, purified control PON1 and PEP-1-PON1 were treated with a Detoxi-Gel™ endotoxin removing gel (Pierce, Rockford, IL, USA) as per manufacturer’s instructions [34]. The Bradford assay was used to estimate protein concentration [37].…”
Section: Methodsmentioning
confidence: 99%
“…Tat peptide is comprised of 9 amino acids (RKKRRQRRR), and it delivers proteins into cells and tissues such as brain cells (20)(21)(22). Several studies, including those undertaken by our group, have demonstrated that various Tat-fused proteins transduce into cells and protect against cell death in various diseases (23)(24)(25)(26)(27)(28)(29).…”
Section: Tat-atox1 Inhibits Streptozotocin-induced Cell Death In Pancmentioning
confidence: 99%
“…The recombinant Tat-ATOX1 plasmid was transformed into Escherichia coli BL21 (DE3; Novagen, Madison, WI, USA) and cultured in 0.5 mM isopropyl-β-D-thiogalactoside (IPTG; Duchefa, Haarlem, The Netherlands) at 18˚C overnight. The harvested cells were purified using an Ni 2+ -nitrilotriacetic acid Sepharose affinity column and PD-10 column chromatography (Amersham, Piscataway, NY, USA) (29,30). The concentration of purified protein was measured using the Bradford assay (Bio-Rad Laboratories, Hercules, CA, USA), as previously described (31).…”
Section: Purification Of Tat-atox1 Protein the Tat Expressionmentioning
confidence: 99%
“…After corneal application of liposome-compacted DNA, transgene expression is scarce and only detectable in the iris, limbus and conjunctiva (82). Internalization of drugs into the corneal epithelium can be achieved (83) as well as transfection of corneal cells with AVV with therapeutic transgenes (84), but gene delivery to the retina via the topical administration route is not currently effective.…”
Section: Delivery Strategies For Non-viral Gene Therapy In the Retinamentioning
confidence: 99%